Peran Lembaga Adat dalam Mendukung Tata Kelola Pemerintahan Lokal di Sumatera Barat - El Darman, Atiqa Azza (LPPM STISIP IMAM BONJOL, 2025)
Abstract This study aims to explore and analyze the strategic role of traditional institutions in supporting local governance in West Sumatra, with a focus on the city of Padang. A qualitative approach was employed to examine the interaction between traditional customary bodies and formal government structures, particularly in the implementation of local values embedded in the philosophy of adat basandi syarak, syarak basandi Kitabullah. Data were collected through in-depth interviews with customary leaders, local government officials, and community members, as well as through direct observation of collaborative practices at the sub-district and village levels. The findings indicate that traditional institutions play a crucial role in mediating between the interests of the community and the government, maintaining social stability, and reinforcing the legitimacy of local policies. However, challenges remain, including overlapping authorities, lack of formal regulation, and limited institutional capacity. This study recommends strengthening the synergy between traditional institutions and local governments through inclusive policies, institutional capacity building, and formal recognition within the framework of local governance.dalam satu paragraf berisikan isu-isu pokok, tujuan penelitian, metode/ pendekatan dan hasil penelitian. Keywords: traditional institutions, local governance, public administration, West Sumatra, institutional collaboration